Obstrucción foliar: uso de estufas de combustión controlada en el cultivo de banano como mecanismos de mitigación. - Lapo Alvarado, Joselyn Veronica; Rojas Hurtado, Cesar Joel (Machala: Universidad Técnica de Machala, 2023)
Headache in banana plants is a physiological disorder that generates abnormalities in the bunch, mainly affecting its weight and fruit quality. It is usually related to the deficiency of C, Zn, Ca, availability of radiation and high relative humidity. The experimental results obtained in different banana plots will be exhibited In the present work located in the Faculty of Agricultural Sciences of the Technical University of Machala on effect of controlled combustion stoves in the mitigation of leaf obstruction, during the development of their phenological stages. A completely randomized block experimental design was carried out with three treatments. The experiments: T-Stoves, T- Foliar and, T- Control, the variables evaluated were: temperature inside the plantation, foliar emission, distance between petioles and number of leaves. Treatment 1 registered slightly high values in all the variables, in terms of foliar emission it displayed homogeneity in the means of treatment 2 and 3, the application of controlled combustion stoves in the early morning hours shows an improvement in terms of development parameters. to the variables evaluated in comparison with the other treatments.
El arrepollamiento en plantas de banano es un desorden fisiológico que genera anormalidades en el racimo, afectando principalmente su peso y calidad de la fruta. Suele relacionarse con la deficiencia de C, Zn, Ca, disponibilidad de radiación y alta humedad relativa., se exhibirán los resultados experimentales obtenidos en distintas parcelas de banano En el presente trabajo ubicadas en la Facultad de Ciencias Agropecuarias de la Universidad Técnica de Machala el efecto de estufas de combustión controlada en la mitigación de la obstrucción foliar, durante el desarrollo de sus estados fenológicos. Se realizó un diseño experimental de bloques completamente al azar con tres tratamientos. Los experimentos: T-Estufas, T-Foliar y T-Testigo, las variables evaluadas fueron: temperatura dentro de la plantación, emisión foliar, distancia entre peciolos y número de hojas. El tratamiento 1 registró valores ligeramente altos en todas las variables, en cuanto a emisión foliar visualizó homogeneidad en las medias del tratamiento 2 y 3, la aplicación de estufas de combustión controlada en horas de la madrugada muestra una mejoría en cuanto a los parámetros de desarrollo a las variables evaluadas en comparación con los demás tratamientos.
Keywords: FERTILIZANTE; EMISION FOLIAR; HOMOGENEIDAD